It's a great big universe: Astrobiology and future trends for an astrotheology. Issue 1 (6th March 2018) - Pryor, Adam
Abstract: Despite the awe and wonder that discoveries related to astrobiology inspire, the sheer volume and diversity of new discoveries related to space science can become overwhelming without meaningful frames of reference by which to organize our understanding of these phenomena. I suggest that a critical feature of the future of "astrotheology" relates to how it serves as an organizing correlate to astrobiology and space research. Considering that the prefix astro‐ has an amplicative and abductive effect on the fields of study to which it is applied, I contend that astrotheology implies a creative and constructive shift in how we conceptualize meaningful human being for theology that parallels how astrobiology effects a creative and constructive shift in how we conceptualize living systems.